Analisis Kurikulum Merdeka dalam Rangka Meningkatkan Mutu Pendidikan Pasca Pandemi di SD Se-Kecamatan Tuntang - A Noreng, Saban; Risniyanti, Indah Dwi (CV. Creative Tugu Pena, 2024)
The Covid-19 pandemic poses challenges in all aspects, especially the educational aspect. The implementation of the learning process due to the Covid-19 pandemic has experienced changes to educational components, including teachers, students, school environment, educational content, educational methods and media as well as the educational curriculum. The aim of the research is to analyze the Independent Curriculum in order to improve the quality of post-pandemic education. This study provides an overview of the implementation of the Independent Curriculum in Tuntang District. The Merdeka Curriculum has three different characteristics from the previous curriculum, namely project-based learning, focus on essential material and learning flexibility. The research method used in this research is descriptive qualitative. The informants in this research were driving teachers and class teachers in the Tuntang District area. Data collection was carried out using several techniques, namely; (a) observation; (b) interview; and (c) documentation. The results of this research are that the implementation of the Merdeka Curriculum in the Tuntang area has been carried out quite well in the first year and the Merdeka Curriculum can be a solution after the pandemic and can improve the quality of education in Indonesia. Keywords: Independent Curriculum, Quality of Education, Post-Pandemic